The Negative Sublime in Coleridge’s Later Poetry; The Irreducibility of Difference - Birlik, Nurten (Journal of History Culture and Art Research, 2014)
Abstract The poetic persona cannot form a fair luminous light embracing the Earth, that is, he cannot activate his creative energy. In Coleridge’s other poems what triggers this energy is Joy and then the mystical power of nature. In this poem his imagination is imprisoned in his consciousness as he cannot feel Joy and the mystical power of nature cannot reconcile the binary oppositions. In his earlier poems nature was a book waiting to be deciphered and Coleridge could read the symbolic language of nature, whereas now, in the absence of Joy, this language is no more accessible to Coleridge and he thematizes the anxiety of this impasse in the poem. As a result, he cannot read the symbols that would make nature into Nature. In other words, he can perceive nature only as empirical reality and cannot perceive what lies beyond or within. This impasse is at the same time a re-formation of the rupture between subject and object that he managed to annihilate in his earlier poems.